2008
DOI: 10.1007/s00134-008-1124-6
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin-B hemoperfusion inactivates circulating proapoptotic factors

Abstract: Objective: To test the hypothesis that extracorporeal therapy with polymyxin B (PMX-B) may prevent Gram-negative sepsisinduced acute renal failure (ARF) by reducing the activity of proapoptotic circulating factors. Setting: Medical-Surgical Intensive Care Units. Patients and interventions: Sixteen patients with Gram-negative sepsis were randomized to receive standard care (Surviving Sepsis Campaign guidelines) or standard care plus extracorporeal therapy with PMX-B. Measurements and results: Cell viability, ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 36 publications
2
75
1
1
Order By: Relevance
“…The main objective of therapeutic apheresis is the removal of toxic substances, although the method can also be applied for immunomodulation. It was reported that the absorption of anandamide by polymyxin B might abolish the diverse negative effects of anandamide, such as hypotension, immunosuppression, and cytotoxicity,53 and that the reduction of serum cytokine levels54 or monocyte mRNA expression,55 and the proapoptotic activity of plasma56 from septic patients might contribute to the efficacy of hemoperfusion with PMX‐F. We previously reported that the expression of HLA‐DR surface antigen on monocytes is decreased in patients with septic shock, and that PMX‐F therapy is effective for increasing its expression 26.…”
Section: Immunological Modification Therapiesmentioning
confidence: 99%
“…The main objective of therapeutic apheresis is the removal of toxic substances, although the method can also be applied for immunomodulation. It was reported that the absorption of anandamide by polymyxin B might abolish the diverse negative effects of anandamide, such as hypotension, immunosuppression, and cytotoxicity,53 and that the reduction of serum cytokine levels54 or monocyte mRNA expression,55 and the proapoptotic activity of plasma56 from septic patients might contribute to the efficacy of hemoperfusion with PMX‐F. We previously reported that the expression of HLA‐DR surface antigen on monocytes is decreased in patients with septic shock, and that PMX‐F therapy is effective for increasing its expression 26.…”
Section: Immunological Modification Therapiesmentioning
confidence: 99%
“…It seems likely that plasma separation techniques can prove to be beneficial in renal injury by removing the pro-apoptotic factors and cytokines. 20 Ghrelin shows a protective effect on kidneys by inhibiting pro-inflammatory cytokines, particularly TNF-α, in the circulation and in kidneys. Ghrelin may thus hold promise for managing endotoxemia-induced AKI.…”
mentioning
confidence: 99%
“…Studies based on the importance of cytokines in this process have offered haemadsorption as a potential strategy to prevent the onset of AKI in sepsis [28]. Extracorporeal therapy with Polymixin B has been shown in some clinical studies to reduce pro-apoptotic factors leading to kidney injury and to reduce organ dysfunction in sepsis [29,30]. Adjunctive treatment with exogenous alkaline phosphatase is currently under investigation for its detoxifying potential [16].…”
Section: Potential Therapiesmentioning
confidence: 99%